DC Motor Controller Using Linear Quadratic Regulator (LQR) Algorithm Implementation on PIC - Mohd Isa, Nur Iznie Afrah (2008)
Linear Quadratic Regulator (LQR) algorithm is one of the controller methods to control a system. In this project, the LQR was implemented on the PIC microcontroller to control the dc motor. The main objective of this controller is to minimize the deviation of the speed of dc motor. Dc motor speed is controlled by its driving voltage. The higher the voltage, the higher the motor speed. The speed of the motor is specifying that will be the input voltage of the motor and the output will be compare with the input. As the result, the output must be the same as or approximately the same as the input voltage. In this project, the LQR algorithm was implemented on the PIC microcontroller so the result can be shown. Before the implementation on the PIC, the dc motor state-space has to be derived. Then, from the state-space, we can design the LQR controller by using the MATLAB software. The stable system is got by tuning the Q and R value that can be seen by the simulation.